Pruning in guava (Psidium guajava) — a review (Current Horticulture, 2024)
Guava a pruning responsive crop. It is usually performed to establish, maintain and adjust the plants for its intended purpose. It is done either to stimulate vegetative growth of plant which are especially low in vigour or to reduce the excessive vegetative growth. It is also done for consistent fruitfulness of trees that have declined in production over the time. Fruit size, quality, yield and crop regulation can be altered by precise pruning technique. Pruning has great influence on tree canopy management under high-density planting system. The pruning intensity has profound effect on flowering and fruit bearing in guava. Severely pruned trees give lower yield with poor quality. For crop regulation trees required to be pruned in May which encourage good crop in winter season. Old and unproductive guava trees can also be revived for good crop, after proper pruning application.
Keywords: Pruning; Rejuvenation; Fruit quality; Canopy regulation; Light interception; Tree growth; Yield